La casa de los espíritus - Allende, Isabel (New York : HarperLibros, 1995)
The epic story of the passionate Trueba family begins at the turn of the century in South America.
Adult
Text in Spanish.
Keywords: Families -- Fiction; Family life -- Fiction; Spanish language; Chile -- Fiction; Chile -- Fiction